High-income households emit more greenhouse gases, primarily due to transport behavior - Sandra Bohmann; Merve Küçük (DIW Weekly Report, 2024)
Greenhouse gas emissions must be reduced by 65 percent compared to 1990 by 2030 to achieve national climate targets. Nearly one third of greenhouse gas emissions in Germany are caused by private household consumption. Using Socio-Economic Panel (SOEP) data, this Weekly Report calculates the amount of CO2 equivalents emitted by households due to residential energy use, nutrition, and transport in Germany. Consumption in these three areas alone results in average emissions that exceed the emissions budget targeted for private individuals more than twofold, with transport and residential energy-related emissions accounting for the largest share of emissions. Emissions increase as income increases, especially in the area of transport, with air travel as the main driver. Meat consumption is the main contributor to nutrition-related emissions, and household size and building type contribute the most to residential energy-related emissions. By identifying the most significant driver of emissions in each of the three areas, targeted political instruments can be identified, such as simplifying housing swaps and the energy-efficient renovation of residential buildings, banning short-haul flights, and introducing an animal welfare levy.
Keywords: Q51; Q58; 330; greenhouse gas emissions; consumption behavior; emissions